Warm Temperature Extremes Across Greenland Connected to Clouds. Issue 9 (27th April 2020) - Gallagher, Michael R.; Chepfer, Hélène; Shupe, Matthew D.; Guzman, Rodrigo
Abstract: Greenland ice sheet melt is a large contributor to rising global sea level and melt is dependent on surface air temperature. Arctic temperatures are strongly coupled to clouds but spatial connections between clouds and temperature have yet to be established across Greenland. By mapping spaceborne lidar measurements and surface observations, it is shown that radiatively opaque clouds generally coincide with anomalously warm near‐surface temperatures at Greenland sites. These results indicate that both temperatures over 0 ° C as well as positive daily temperature anomalies relate to spatially extensive opaque cloud cover. While prior studies indicate that clouds enhance extreme melt events, this research shows that opaque cloud cover and surface warming are closely related across the Greenland ice sheet, particularly in the ablation region. These findings establish broadly the spatial relationships between opaque clouds and temperatures and demonstrate the importance of direct observations across Greenland. Plain Language Summary: Greenland ice sheet melt linked to temperatures is a large contributor to rising global sea level. Arctic temperatures are related to cloud cover but spatial changes in clouds and temperature for Greenland have yet to be quantified. Here we show that a specific type of clouds, determined by a measurement signature, coincide with warm temperatures at the Greenland surface. These results indicate that unusual occurrences of temperatures above 0 ° C relate closely to cloud cover. While prior work has shown that clouds enhance extreme melt events, this research shows that cloud cover and surface warming are closely tied across the Greenland ice sheet, particularly in the regions of high mass loss. These findings establish the variability in clouds and demonstrate the importance of direct observations across Greenland. Key Points: Daily variability of opaque cloud cover and temperatures are closely linked Anomalies in opaque clouds and temperatures are tied to circulation regime The largest positive anomalies in both opaque clouds and temperatures relate to days with southerly transport